Health Behaviors in Pregnant Women with Psychological Problems and Disorders: Scoping Review - Bayti Jannah Bayti; Cesa Septiana Pratiwi (Women, Midwives and Midwifery, 2023)
Background: The negative impact of anxiety on the mother is changes in the behavior of pregnant women such as diet, lifestyle or physical activity, resulting in labor complications, anxiety problems in the puerperium period. While the impact on the baby such as stunted fetal growth, preterm birth, asphyxia, Low Birth Weight (LBW) and can even cause death in the baby. Objective: To review scientific evidence based on published articles related to the health behavior of pregnant women with psychological problems and disorders. Methods: This research method was a scoping review, using PEO framework. Literature search used PubMed, ScienceDirect, Wiley Online Library, and grey literature using Google Scholar and Research Rabbit. Articles were critically appraised by using JBI and MMAT critical appraisal tools. Results: There were 7 articles out of 7,796 that were relevant to the research objectives. The articles come from 4 developed countries and 3 developing countries. Three themes were found namely health behavior, the impact of anxiety, and stress reduction strategy. Conclusion: Based on the 7 articles obtained, the health behavior of pregnant women is in accordance with the objective are knowing compliance with ANC visits in pregnant women, knowing health behavior related to consumption of nutritious food in pregnant women, knowing the physical activity of pregnant women with psychological problems and disorders.